Nanostructured organic layers via polymer demixing for interface-enhanced photovoltaic cells - Castro, Fernando A. [UNESP]; Benmansour, Hadjar [UNESP]; Nüesch, Frank [UNESP]; Hany, Roland [UNESP]; Graeff, Carlos F.O. [UNESP]; Tutis, Eduard (My University, 2006)
Nanostructured, semiconducting polymer films were prepared via vertical demixing of MEHPPV/ polystyrene blends during spin-coating, combined with selective dissolution. This allowed the fabrication of efficient bilayer MEHPPV/ C60 photovoltaic device architectures with a large interface area and selective charge transport pathways at the same time.